Organization of the Educational Process: Opportunities for Individualization of Training - B. A. Sazonov (Высшее образование в России)
The possibilities of real individualization of education in Russian universities are constrained by the peculiarities of the type of organization of the educational process. Almost all Russian universities are characterized by stream-group organization of training, in which study groups and streams are formed once for the entire period of study. Students of each study group during the entire period of study have a common curriculum and a common schedule of training sessions. Opportunities for individualization of curricula and programs are very limited and confined to the choice of a foreign language and one of several disciplines of the socio-economic cycle. In modern higher education, the stream-group organization of education is preserved only in Russian universities, universities of the post-soviet and partially post-socialist space. Most universities in the rest of the world uphold the principles of individually-oriented organization of training, according to which each student has an opportunity to choose from the curriculum modules to study in the next semester, choose the teachers and the time of classes. In accordance with the choice of students, groups and streams are formed, which retain only during the current semester. Thus, we emphasize, not individual persons but all the students of modern universities have individual curricula and schedules of training sessions. The article discusses the opportunities and prospects of the individualization of education at Russian universities.